Implementation Al- qawā ʿ id Al- fiqhiyyah Al- asāsiyyah in Islamic Economics through Donation-Based Crowdfunding - Sari Damayanti; Hasan Bisri; Ayi Yunus Rusyana; Sri Dewi Anggadini (LP2M IAIN Palopo, 2026)
Abstract This article examines the implementation of al-qawā ʿid al-fiqhiyyah al-asāsiyyah in contemporary Islamic economic practices, particularly in the donation-based crowdfunding model. Fiqhiyyah principles are general guidelines that can be applied to address modern muamalah issues. With the development of financial technology, donation-based crowdfunding practices have become a popular new socio-economic instrument in Indonesia and the world. This analysis shows that the five main fiqhiyyah principles (al-umūr bi maqāsidihā, al-yaqīn lā yazūlu bi al-syakk, al-masyaqqah tajlib al-taysīr, al- ḍ arar yuzāl, al- ʿ ādah mu ḥ akkamah) can be used as a legal basis to ensure that donation-based crowdfunding runs according to sharia principles, is safe, and beneficial to society. This article also discusses crowdfunding theory, the history and development of crowdfunding institutions, the problems faced, as well as solutions and future prospects. Keywords: Qawā ʿ id Fiqhiyyah, Crowdfunding, Islamic Economics, Donations, Muamalah .